2022
DOI: 10.3390/rs14133163
|View full text |Cite
|
Sign up to set email alerts
|

SRT: A Spectral Reconstruction Network for GF-1 PMS Data Based on Transformer and ResNet

Abstract: The time of acquiring remote sensing data was halved after the joint operation of Gao Fen-6 (GF-6) and Gao Fen-1 (GF-1) satellites. Meanwhile, GF-6 added four bands, including the “red-edge” band that can effectively reflect the unique spectral characteristics of crops. However, GF-1 data do not contain these bands, which greatly limits their application to crop-related joint monitoring. In this paper, we propose a spectral reconstruction network (SRT) based on Transformer and ResNet to reconstruct the missing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In this study, the mean relative error (MRAE) and root mean square error (RMSE) are selected as evaluation metrics for spectral reconstruction [ 31 , 32 ]. MRAE is utilized to measure the average relative error between the reconstructed spectra and the actual spectra, as defined by Equation (1).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the mean relative error (MRAE) and root mean square error (RMSE) are selected as evaluation metrics for spectral reconstruction [ 31 , 32 ]. MRAE is utilized to measure the average relative error between the reconstructed spectra and the actual spectra, as defined by Equation (1).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the continuous development of remote-sensing satellite technology has made acquiring remote-sensing images easy. 4,5,6,7,8 High-resolution remote sensing images can provide finer spectral, texture, and other features, and fast and accurate extraction of roads from high-resolution remote sensing images is a convenient and effective method for road extraction. 9,10,11,12 However, remote sensing satellite images are taken from a high altitude, so they cover a wide area.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining detailed and accurate road information plays a critical role in urban planning, 1 autonomous driving, 2 geographic information system upgrading, 3 and other fields. In recent years, the continuous development of remote-sensing satellite technology has made acquiring remote-sensing images easy 4 , 5 , 6 , 7 , 8 . High-resolution remote sensing images can provide finer spectral, texture, and other features, and fast and accurate extraction of roads from high-resolution remote sensing images is a convenient and effective method for road extraction 9 , 10 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…We opted for the convolutional architecture instead of a recurrent alternative due to its training and inference efficiency. The ResNeXt architecture was chosen due to the versatility of ResNet-type [18] architectures, which allows for the design of models that can be customized for specific tasks by stacking multiple blocks of the same type. Moreover, we empirically showed that the inclusion of multiple past radar measurements led to more accurate predictions further in the future.…”
Section: Introductionmentioning
confidence: 99%